Temporal variation in zooplankton and phytoplankton community species composition and the affecting factors in Lake Taihu—a large freshwater lake in China. (February 2019) - Li, Cuicui; Feng, Weiying; Chen, Haiyan; Li, Xiaofeng; Song, Fanhao; Guo, Wenjing; Giesy, John P.; Sun, Fuhong
Abstract: Monitoring diverse components of aquatic ecosystems is vital for elucidation of diversity dynamics and processes, which alter freshwater ecosystems, but such studies are seldom conducted. Phytoplankton and zooplankton are integral components which play indispensable parts in the structure and ecological service function of water bodies. However, few studies were made on how zooplankton and phytoplankton community may respond simultaneously to change of circumstance and their mutual relationship. Therefore, we researched synchronously the phytoplankton communities as well as zooplankton communities based on monthly monitoring data from September 2011 to August 2012 in heavily polluted areas and researched their responses to variation in environmental parameters and their mutual relationship. As indicated by Time-lag analysis (TLA), the long-term dynamics of phytoplankton and zooplankton were undergoing directional variations, what's more, there exists significant seasonal variations of phytoplankton and zooplankton communities as indicated by Non-Metric Multidimensional scaling (NMDS) methods. Also, Redundancy Analysis (RDA) demonstrated that environmental indicators together accounted for 25.6% and 50.1% variance of phytoplankton and zooplankton, respectively, indicating that environmental variations affected significantly on the temporal dynamics of phytoplankton as well as zooplankton communities. What's more, variance partioning suggested that the major environmental factors influencing variation structures of zooplankton communities were water temperature, concentration of nitrogen, revealing the dominating driving mechanism which shaped the communities of zooplankton. It was also found that there was significant synchronization between zooplankton biomass and phytoplankton biomass (expressed as Chl-a concentration), which suggested that zooplankton respond to changes in dynamic structure of phytoplankton community and can initiate a decrease in phytoplankton biomass through grazing in a few months. Graphical abstract: Highlights: Seasonal variation of phytoplankton and zooplankton community specieswere investigated with NMDS ordination method. Significant environmental parameters affected phytoplankton and zooplankton were identified with Redundancy analysis. Synchronous variation of phytoplankton and zooplankton was discussed. Variation of phytoplankton and zooplankton were primarily explained by water temperature and nitrogen.